2016
DOI: 10.1007/s00216-016-9913-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 12 pharmaceuticals in water samples by ultrasound-assisted dispersive liquid–liquid microextraction coupled with ultra-high performance liquid chromatography with tandem mass spectrometry

Abstract: A new analytical method was developed for simultaneous determination of 12 pharmaceuticals using ultrasound-assisted dispersive liquid-liquid microextraction (DLLME) followed by ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS). Six nonsteroidal anti-inflammatory drugs (NSAIDs, ketoprofen, mefenamic acid, tolfenamic acid, naproxen, sulindac, and piroxicam) and six antibiotics (tinidazole, cefuroxime axetil, ciprofloxacin, sulfamethoxazole, sulfadiazine, and chloramphenico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In most samples of surface water, chloramphenicol was below the LOD. In Shenyang, China, Guan et al determined 297 ng/L in WWTP influent and less than the LOD in river water samples [37], while Li et al reported concentrations from below the LOD to 635 ng/L [38]. Camacho-Munoz et al did not detect chloramphenicol in any samples taken from two WWTPs in Western and Northern Europe [39].…”
Section: Detecting the Presence Of Selected Antibiotics In Water Samplesmentioning
confidence: 99%
“…In most samples of surface water, chloramphenicol was below the LOD. In Shenyang, China, Guan et al determined 297 ng/L in WWTP influent and less than the LOD in river water samples [37], while Li et al reported concentrations from below the LOD to 635 ng/L [38]. Camacho-Munoz et al did not detect chloramphenicol in any samples taken from two WWTPs in Western and Northern Europe [39].…”
Section: Detecting the Presence Of Selected Antibiotics In Water Samplesmentioning
confidence: 99%
“…While higher sensitivity has been achieved for the detection of tolfenamic acid using a UPLC-MS/MS method with of LOD 0.076 ng/mL and LOQ 0.216 ng/mL in wastewater (Guan et al, 2016), the method required concentration of the samples using solid-phase extraction (SPE) methods. SPE has been reported for the extraction and purification of benzbromarone and tolfenamic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Detection methods for benzbromarone and tolfenamic acid have been developed for several animal and human tissues as well as wastewater (Beyer et al, 2005;Gallo et al, 2008;Guan et al, 2016) however, methods for the simultaneous analysis of benzbromarone and tolfenamic acid from plant tissue are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, before using chromatographic or hyphenated techniques sample enrichment is an essential step. The most common sample enrichment techniques to detect antibiotic residues are liquid-liquid extraction (LLE) [23,24], dispersive liquid-liquid microextraction [25,26], solid-phase extraction [27,28], solid-phase microextraction [29,30,31], pressurized liquid extraction [32,33], matrix solid-phase dispersion extraction [34,35], and the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method [36,37]. Among these methods, SPME has gained popularity owing to its superior features such as low cost, high extractability, almost solventless uses and easy to operate technique.…”
Section: Introductionmentioning
confidence: 99%